Evaluation of the vascularity of an isolated bowel segment using fluorescein angiography in rats - Chandrasekharam V.V.S.S; Talwar D; Bhatnagar V (Wolters Kluwer Medknow Publications, 2007)
Aims: An isolated bowel segment (IBS), a viable loop of bowel completely free of its mesenteric attachments, has potential clinical use in bowel lengthening and other techniques. The end point of successful creation of an IBS is the development of adequate collateral circulation. In this experimental study, we report the use of fluorescein test to demonstrate collateral vascularity of the IBS in rats. A simple technique for the visualization and photography of fluorescein in the tissues is also described. Materials and Methods: In nine Wistar rats, 5 cm of distal ileum was anastomosed side-to-side to 5 cm of proximal colon using 6/0 PDS. In one rat (control), the colon patch was isolated from the rest of the large bowel immediately and fluorescein test was performed. The remaining eight (study group) rats were operated after 8 weeks and the procedure followed as in the control rat. In the last rat, the mesentery of the colon patch was severed; and 2 weeks later, the fluorescein test was performed. Results: The colon patch in the control rat showed complete lack of fluorescence; in the seven rats tested after 8 weeks, patchy fluorescence was demonstrated in the colon patch; and in the last rat, bright fluorescence of the whole patch could be demonstrated within a few seconds following fluorescein injection. Conclusion: This study describes a simple technique for the fluorescein test. The observation that the vascular collaterals were more abundant after mesocolic division was obviously due to the opening up of collaterals over a period of time. The fluorescein test is a rapid and easy test and can be easily reproduced.